Complete Genome Sequence of Clostridium clariflavum DSM 19732. Issue 1 (January 2012) - Izquierdo, Javier; Goodwin, Lynne; Davenport, Karen; Teshima, Hazuki; Bruce, David; Detter, Chris; Tapia, Roxanne; Han, Shunsheng; Land, Miriam; Hauser, Loren; Jeffries, Cynthia; Han, James; et al.
Abstract Clostridium clariflavum is a Cluster IIIClostridium within the familyClostridiaceae isolated from thermophilic anaerobic sludge (Shiratori et al, 2009). This species is of interest because of its similarity to the model cellulolytic organismClostridium thermocellum and for the ability of environmental isolates to break down cellulose and hemicellulose. Here we describe features of the 4, 897, 678 bp long genome and its annotation, consisting of 4, 131 protein-coding and 98 RNA genes, for the type strain DSM 19732.